Hubungan Asupan Protein Dan Kadar Albumin Pada Pasien Kanker Di Rumah Sakit Roemani Muhammadiyah Semarang - Hapsari Sulistya Kusuma; Maghfiroh -; Sufiati Bintanah (Jurnal Gizi, 2014)
Cancer is a disease caused by the growth of body tissue cells are abnormal and out of control and can disrupt and damage the cells of other tissues. Malnutrition is a condition that often occurs in patients with cancer. We investigated the associations of protein intake with albumin levels in cancer patienst at Roemani Muhammadiyah Hospital Semarang. This research was explanatory research, to determined the association between the variables in the study. There were 14 samples, were taken using purposive sampling method. Univariate analysis was used to present frequency, tendency and standard deviation. Bivariate analysis using Pearson correlation. Protein intake was associated with albumin levels positively (p=0,030,r=0,513). There was a association of protein intake with albumin levels in cancer patients at Roemani Muhammadiyah Hospital Semarang.